If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 14 = 82 + -8x Reorder the terms: 14 + 4x = 82 + -8x Solving 14 + 4x = 82 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 14 + 4x + 8x = 82 + -8x + 8x Combine like terms: 4x + 8x = 12x 14 + 12x = 82 + -8x + 8x Combine like terms: -8x + 8x = 0 14 + 12x = 82 + 0 14 + 12x = 82 Add '-14' to each side of the equation. 14 + -14 + 12x = 82 + -14 Combine like terms: 14 + -14 = 0 0 + 12x = 82 + -14 12x = 82 + -14 Combine like terms: 82 + -14 = 68 12x = 68 Divide each side by '12'. x = 5.666666667 Simplifying x = 5.666666667
| 53-3x=8x-20 | | (m-3)(m-3)=64 | | m^2-9-64=0 | | 3x-34=2x-5 | | 4/x+1=2x/x+6 | | 195-3x=33x+23 | | 33=6c-3 | | -86-7x=8x+149 | | rd=309d | | 30f=f^2 | | 4(-1x-3)=-52 | | 7(4x+1)=-91 | | 8-7x=x-48 | | -7x-1=-5x-11 | | 6-3x-3x=-12 | | 5x+3+x=-33 | | 5(-8+4x)=160 | | 3(-8+7x)=102 | | 10+4x=x-2 | | 6x-6=-3x-60 | | (-22)-[7+(-6)]= | | -7-5x+3x=13 | | 7x+8+6x=47 | | [(-22)-7]+(-6)= | | (x+a)(x+3)=x^2-2a-15 | | 1=125000+3000x | | 9x^3+6kx^2+(1-3k)x=0 | | (2k-7)(2k-3)=0 | | 7m+21=3+33 | | x^2-4x+k=0 | | 7x-5=10-3x | | 2x-17=-39 |